Depth and material sensitivity in magneto–optic nanostructures. (7th May 2012) - Postava, K.; Hamrle, J.; Hamrlová, J.; Hrabovskš, D.; Životskš, O.; Pištora, J.; Lukáš, D.
Magneto–optic (MO) methods are used for characterisation of magnetic ultrathin lms and nanostructures. The paper deals with the sensitivity of the complex MO effect to lms at different depths and to different materials in periodic multilayers and self assembled nanostructures. It is shown, that the basic principle and separation methods are the same for depth sensitive selectivity and the material sensitivity in nanostructures. Method of MO signal separation from different lms and phases and the gure of merit used to quantify the MO ellipsometric selectivity of magnetic nanostructures is dened on the basis of linear matrix algebra. We review applicability of the method to separate MO contributions from (Au/Co)N, N = 2, 3; (Co/Au/NiFe/Au)10 multilayers; BiFeO3 –CoFe2 O4 self–assembled nanostructure; cobalt lm on self–organised Au islands; and magnetically hard Fe nanoparticles near the surface of soft FeNbB amorphous ribbons.